(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
The therapeutic chemical constituents’ investigation of Senecio biafrae shoot and Vernonia amygdalina leaf, which are commonly used in the Nigerian ethnomedicine, were studied. Phytochemicals viz: cardiac glycosides, tannin, cyanogenic glycosides, flavonoid, alkaloid and saponin in the dried powdered plants samples were analysed quantitatively by spectrophotometric and titrimetic methods. In the results, cardiac glycoside was the most abundant in V. amygdalina (8.79 ± 0.02 mg/g [or 57.1 %]) and S. biafrae (6.07 ± 0.07 mg/g [or 42.24 %]), with the former significantly (P<0.01) higher. Flavonoid (5.79 ± 0.08 mg/g [or 28.3 %]) and tannin (0.47 ± 0.02 mg/g [or 3.1 %]) contents in V. amygdalina were higher in comparison with the flavonoid (3.55 ± 0.01 mg/g [or 24.70 %]) and tannin (0.28 ± 0.01 mg/g [or 1.95 %]) in S. biafrae. The alkaloid in S. biafrae (4.1 ± 0.04 mg/g [or 28.53 %]) was higher in comparison with that of V. amygdalina (0.1± 0.01 mg/g [or 0.6 %]). The cyanogenic glycosides (0.26 ± 0.006 mg/g [or 1.81 %]) in S. biafrae was more in comparison with that of V. amygdalina (0.12 ± 0.02 mg/g [or 0.3 %]). The saponin content of V. amygdalina (0.13 ± 0.04 mg/g [or 0.6 %]) and S. biafrae (0.11 ± 0.03 mg/g [or 0.77 %]) were relatively low with no significant difference. However, the presence of these therapeutic secondary metabolites in S. biafrae and V. amygdalina supports their uses in the herbal preparations for the treatment of some diseases like malaria, diabetes and infertility in Nigeria.